Improving the targeting of fertilizer subsidy programs in Africa south of the Sahara: Perspectives from the Ghanaian experience - Houssou, Nazaire; Asante-Addo, Collins; Andam, Kwaw S. (International Food Policy Research Institute, 2017)
This paper assesses whether fertilizer subsidy programs can be better targeted to resource-poor farmers using the case of Ghana and proxy means test approaches. Past fertilizer subsidy programs in the country have not been particularly targeted to the poor, even as targeting poor and smallholder farmers has become key in the program implementation guidelines. As a result, many poor farmers have not benefited from past programs. Our results show that targeting approaches based on proxy means tests that use the correlates of poverty to select beneficiary farmers can potentially improve the poverty outreach and costeffectiveness of Ghana’s fertilizer subsidy programs. Therefore, we propose that the proxy means test approach should be considered for implementing Ghana’s fertilizer subsidy programs, first in a pilot project involving a few communities, and later, if found successful, in a full-scale program.